Fine tuning of tensile properties in CrCoNi medium entropy alloy through cold rolling and annealing. (October 2019) - Sathiyamoorthi, Praveen; Asghari-Rad, Peyman; Bae, Jae Wung; Kim, Hyoung Seop
Abstract: In the present study, tensile properties of CrCoNi medium entropy alloy with different microstructures (recovery, partial recrystallization, recrystallization) were investigated by subjecting cold-rolled samples to different annealing conditions. The microstructure of the cold-rolled sample showed the presence of severely deformed grains with several deformation twins. Annealing of the cold-rolled samples at 700 °C and above for 60 min led to fully recrystallized microstructure, while annealing at temperatures lower than 700 °C led to recovery and partially recrystallized microstructures. The annealed samples showed a typical strength-ductility trade-off with an increasing fraction of recrystallized grains and increasing average grain size in samples with partially recrystallized and fully recrystallized microstructure, respectively. Fine tuning of microstructure led to a remarkable combination of strength ( 1 GPa) and uniform elongation (28%) in the sample with partially recrystallized microstructure, which consists of 77% of recrystallized grains with an average recrystallized grain size of 3 μm. Highlights: Fine tuning of microstructure through cold rolling and annealing. A reasonable ductility requires minimum of 55% of recrystallized grains. Optimal tensile properties achieved in sample with 77% recrystallized grains. Combination of strengthening from back stress and Hall-Petch effect.